Analisis Produksi Pakan Mandiri Di Pokdakan Pinang Raya, Desa Pinang Sebatang, Kabupaten Bangka Tengah - Nabila, Salwa; Hidayah, Nurul; Pebriyandi; Pratama, Aditya Murrey; Rahman, Taufiqur (Jurnal Perikanan dan Kelautan, 2025)
Feed is the largest operational cost element in fish farming, accounting for 60-80% of total production expenditure. The volatility of feed raw material prices and dependence on commercial feed is a challenge for farmers, especially small and medium enterprises. The independent fish feed movement emerged as a solution to reduce production costs by 30-40%, giving farmers control over quality and nutritional composition. This study was conducted at Pokdakan Pinang Raya, Pinang Sebatang Village, Central Bangka Regency, to analyze independent feed production. Data collection methods included observation and interviews, with a focus on improving the knowledge and skills of farmers. The results showed that the initial capital for independent feed came from group contributions, with a profit of 100% compared to commercial feed. The production process uses diesel engines and pays attention to the nutritional needs of fish. The independent feed is marketed locally and supported by the government. This program not only reduces feed costs, but also supports environmental sustainability.